2011
DOI: 10.1248/cpb.59.1386
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effect of Liposomal Histone Deacetylase Inhibitor-Lipid Conjugates in Vitro

Abstract: Histone deacetylase inhibitor (HDACI), suberoylanilide hydroxamic acid (SAHA), approved by the Food and Drug Administration (FDA) for the treatment of cutaneous T cell lymphoma, is a promising new treatment strategy for various cancers. In this study, we hypothesized that a liposomal formulation of HDACI might efficiently deliver HDACI into tumors. To incorporate HDACI efficiently into the liposomal membrane, we synthesized six HDACI-lipid conjugates, in which polyethylene glycol(2000) (PEG(2000))-lipid or cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The possible mechanism for the comparable or even further enhanced efficacy in histone acetylation is that POEG- b -PSAHA protected the hydroxamic acid of SAHA from hydrolysis and pharmacologically active SAHA was slowly released from the polymer over a prolonged period of time. On the other hand, free SAHA with unprotected hydroxamic acid may be subjected to rapid metabolic conversion to inactive metabolites, SAHA-glucuronide and 4-anilino-4-oxobutanoic acid (Hattori et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The possible mechanism for the comparable or even further enhanced efficacy in histone acetylation is that POEG- b -PSAHA protected the hydroxamic acid of SAHA from hydrolysis and pharmacologically active SAHA was slowly released from the polymer over a prolonged period of time. On the other hand, free SAHA with unprotected hydroxamic acid may be subjected to rapid metabolic conversion to inactive metabolites, SAHA-glucuronide and 4-anilino-4-oxobutanoic acid (Hattori et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…15,16) HDAC inhibitors have been applied to treatment of human cancers. 17,18) Zolinza (vorinostat, SAHA) was approved by the Food and Drug Administration (FDA) for the treatment of advanced cutaneous T-cell lymphoma (CTCL). 19) A benzamide HDAC inhibitor, MS275, is reported to be a selective HDAC inhibitor targeting class I HDACs, which is a moderately potent HDAC inhibitor in phase II clinical trial.…”
Section: -7)mentioning
confidence: 99%
“…Recently, liposomes have gained potential interest in the field of biotechnology therapeutics as delivery systems for recombinant proteins, antisense oligonucleotides and cloned genes. With the recent development in the field, several companies are actively engaged in expansion and evaluation of liposome products for anticancer, antifungal therapy and for prophylaxis therapy [7][8][9][10][11][12][13][14][15]. It is demonstrated that liposomes have potential impact in submiocron and nano-scale reaction engineering.…”
Section: Introductionmentioning
confidence: 99%